The Italian food environment may confer protection from hyper-palatable foods: evidence and comparison with the United States - Fazzino, Tera L.; Summo, Carmine; Pasqualone, Antonella (Frontiers in Nutrition, 2024)
Background: Multi-national food corporations may saturate country-level food systems with hyperpalatable foods. However, the degree to which global food corporations have been integrated into country-level food systems may vary. Italy has largely retained local food production and may have low hyper-palatable food (HPF) availability in the food supply. The study quantified the prevalence of HPF in the Italian food system and compared the hyper-palatability of similar foods across Italy and the United States, which has wide HPF saturation.Methods: A national food system dataset was used to characterize HPF availability in Italy. A representative sample of foods commonly consumed in both Italy and the US were collected and compared. Foods represented six categories: cookies/biscotti, cakes/merendine, salty snacks, industrial bread, frozen pizza and protein/cereal bars. A standardized definition from Fazzino et al (2019) identified HPF.Results: Less than one third (28.8%) of foods in the Italian food system were hyper-palatable. US HPF items had significantly higher fat, sugar, and/or sodium across most food categories (p values= .001 to .0001). Italian HPF items had higher fiber and/or protein relative to US HPF from the same category (p values = .01 to .0001).The Italian food system may confer protection from HPF exposure. HPF products in Italy had lower palatability-related nutrients and higher satiety-promoting nutrients.